Ultrathin Zn-Gallate Catalyst: A Remarkable Performer in CO2 and Propylene Oxide Polymerization - Yang, Yongmoon; Sung, Kihyuk; Lee, Jong Doo; Ha, Junho; Kim, Heeyoun; Baek, Jinsu; Seo, Jeong Hwa; Kim, Seung Joo; Lee, Bun Yeoul; Son, Seung Uk; Kim, Byeong Su; Kim, Yongsun; et al. (ACS Sustainable Chemistry and Engineering, 2024)
Zn-gallate, an innovative catalyst synthesized using cost-effective zinc salts and gallic acid without complicated synthetic procedures, has been successfully applied in the copolymerization of CO2 and propylene oxide. Zn-gallate displays exceptionally thin sheets with a thickness of 1-2 nm, leading to remarkable catalytic activity, high carbonate linkage proportion, and minimal monomer formation (3.01 kg/g-cat, fCO2 = 0.97, and selectivity 91%). Zn-gallate outperforms other heterogeneous catalysts for the polymerization of CO2 and propylene oxide. Furthermore, the polycarbonates synthesized using Zn-gallate exhibit substantially high molecular weights. A comprehensive characterization of Zn-gallate has been undertaken, employing SEM, TEM, BET, AFM, PXRD, IR, CP-TOSS 13C NMR, XPS, TGA, and ICP analyses, which provided valuable insights into the exceptional catalytic properties of this novel catalyst.
Keywords: CO2 polymer; CO2 utilization; Gallate; Polypropylene carbonate; Propylene oxide; Synthesised; Ultra-thin; Ultrathin catalyst; Zn-gallate; ]+ catalyst; CO2 polymer; CO2 utilization; polypropylene carbonate; ultrathin catalyst; Zn-gallate